Towards an Integrated Approach of Conducting Fungal Research in Costa Rica - Rojas-Alvarado, Carlos (2019)
Costa Rica is a small country in Central America with a recent history of fungal research. However, comparative differences with other territories in the Mesoamerican Biodiversity Hotspot region have promoted the study of fungi and the integration of fungal information with natural resource management. Even though there is still a large number of multidisciplinary aspects to cover in Costa Rica for robust incorporation of fungal data in conservation and political and developmental agendas, regional advantages have allowed this country to move towards such goal more rapidly than other countries in this part of the world. Mycoliteracy-centered and citizen science initiatives seem to be the next step in order to normalize disparities in fungal perception across regions within the country and promote social interaction with fungi. However, in general terms, the Costa Rican society seems to be aware of the potential of fungi as a source of food and medicines and their remarkable contribution through ecosystem services. In this manner, fungal conservation and management seem easier to conduct in this territory than in other regions of the world where less information on fungi has reached the general population.